Effects of Partial Organic Substitution for Chemical Fertilizer on Antibiotic Residues in Peri-Urban Agricultural Soil in China - Baocheng Dong; Wei Li; Wenyong Xu (Antibiotics, 2021)
Recycling of organic wastes in agricultural ecosystems to partially substitute chemical fertilizer is recommended to improve soil productivity and alleviate environmental degradation. However, livestock manure- and sewage sludge-derived amendments are widely known to potentially carry antibiotic residues. The aim of this study is to investigate how substituting organic fertilizer for chemical fertilizer affects soil quality and antibiotic residues in agricultural soil, as well as their tradeoffs. A field experiment was conducted with the different treatments of pig manure and sewage sludge as typical organic fertilizers at equal total nitrogen application rates. The analysis of variance showed that the increments on the levels of residual antibiotics in the agricultural soils due to organic substitution for chemical fertilizer by pig manure and sewage sludge were observed. The antibiotic residues ranged from 13.73 to 76.83 ng/g for all treatments. Partial organic substitution significantly increased the sequestration of antibiotics in agricultural soil by 138.1~332.5%. Organic substitution will also significantly improve soil quality, especially for nutrient availability. Based on principal component analysis, organic substitution will strongly affected soil quality and antibiotic contamination. Pearson’s correlation showed that soil physicochemical properties had significant correlations with concentrations of antibiotics in soil, indicating organic fertilizers can promote the persistence of antibiotics in soil by modifying soil quality. To balance the benefits and risks, appropriate management practices of organic fertilizers should be adopted.